Visiting Professor As Implementation Of Cooperation Between Universitas Islam Negeri Sultan Syarif Kasim Riau And Arkalyk Pedagogical Institute, Kazakhstan - Hamzah, Muhammad Luthfi; Nazaruddin, Nazaruddin; Saule, Baizakova; Perizat, Azhibekova; Medet, Ilubaev; Ainur, Sundetbaeva; Zhannar, Baisoteva (Yayasan Riset dan Pengembangan Intelektual, 2024)
Visiting Professor Program (VIPP) is a program to send PTAI professors to universities / research institutions abroad with a maximum duration of 1 month, facilitating PTAI permanent lecturers with the title of Professor to develop their ideas and ideas through joint research, updating teaching materials and learning methods in accordance with the latest developments in the world of international education, developing curriculum studies, comparative studies of institutional management management, and become a guest examiner for students of overseas partner universities. Purpose of Visiting Professor Program (VIPP) Increasing PTAI institutional competitiveness towards a world class university through cooperation and partnership with foreign universities / institutions, Development of competence of PTAI professors in the fields of research, academic writing and networking abroad through scientific presentations, research, benchmarking, publishing manuscripts in reputable international journals Socialization and internationalization of Nusantara Islamic studies. This VP program is an implementation of international cooperation between UIN Sultan Syarif Kasim and Arkalyk Pedagogical Institute, Kazakhstan. This highly talented young lecturer and reviewer of several international journals indexed by Scopus is listed as the only lecturer from the State Islamic Religious College (PTKIN) in Indonesia teaching at the university.